Knockdown of wfs1, a fly homolog of Wolfram syndrome 1, in the nervous system increases susceptibility to age- and stress-induced neuronal dysfunction and degeneration in Drosophila. - Sakakibara, Y.; Sekiya, M.; Fujisaki, N.; Quan, X.; Iijima, K.M. (PLoS Genetics, 2018)
Wolfram syndrome (WS), caused by loss-of-function mutations in the Wolfram syndrome 1 gene (WFS1), is characterized by juvenile-onset diabetes mellitus, bilateral optic atrophy, and a wide spectrum of neurological and psychiatric manifestations. WFS1 encodes an endoplasmic reticulum (ER)-resident transmembrane protein, and mutations in this gene lead to pancreatic ?-cell death induced by high levels of ER stress. However, the mechanisms underlying neurodegeneration caused by WFS1 deficiency remain elusive. Here, we investigated the role of WFS1 in the maintenance of neuronal integrity in vivo by knocking down the expression of wfs1, the Drosophila homolog of WFS1, in the central nervous system. Neuronal knockdown of wfs1 caused age-dependent behavioral deficits and neurodegeneration in the fly brain. Knockdown of wfs1 in neurons and glial cells resulted in premature death and significantly exacerbated behavioral deficits in flies, suggesting that wfs1 has important functions in both cell types. Although wfs1 knockdown alone did not promote ER stress, it increased the susceptibility to oxidative stress-, excitotoxicity- or tauopathy-induced behavioral deficits, and neurodegeneration. The glutamate release inhibitor riluzole significantly suppressed premature death phenotypes induced by neuronal and glial knockdown of wfs1. This study highlights the protective role of wfs1 against age-associated neurodegeneration and furthers our understanding of potential disease-modifying factors that determine susceptibility and resilience to age-associated neurodegenerative diseases.